ANALYSIS OF THE POSSIBILITIES OF LONG-TERM STORAGE OF DATA ON DNA - Kryuchyn, A. A.; Belyak, Ie. V.; Kryuchyna, Ye. A.; Shikhovets, A. V. (Medical Informatics and Engineering, 2021)
Background. For several decades, progress in storage technologies has been measured primarily in terms of storage capacity and data read / write speed, with the amount of information generated increasing every day. The purpose of the study was to analyze the various technologies used to store digital data on DNA, the pros and cons of each of the methods used, as well as the advantages and limitations of using DNA as an information carrier. Materials and methods. Results. The reliance on DNA as a dense storage medium with high storage capacity and its ability to withstand extreme environmental conditions has increased over the past few years. The presented work presents the results of a critical analysis of the prospects for using DNA memory for long-term storage of information. It is shown that DNA memory provides both information recording with a high recording density and its long-term storage. These data indicate that DNA memory technologies can contribute to significant changes in the archival storage of data. The analysis of the areas of application of DNA memory, codes used to represent data in DNA memory. A number of approaches to the design of DNA codons and data storage are analyzed in detail, certain pros and cons of each of them. Conclusions. Methods of steganography using DNA molecules for the safe storage of information are discussed. At the same time, the high cost of DNA, the impossibility of quick access to information, the need for expensive equipment for reading and writing makes this type of storage device still suitable for limited use.